Ukraine invasion - mass blocks (Russia) - Voidly (Voidly Global Censorship Index, 2022)
CRITICAL severity censorship detected in Russia. Data sourced from OONI.
Censorship Incident ID: RU-2022-0001. Severity: critical. Confidence: 95%